Maternally inherited diabetes and deafness with a variable presentation across three generations within a pedigree, South Africa - Herbert Makgopa; Tanja Kemp; Surita Meldau; Engela M. Honey; Bettina Chale-Matsau (AOSIS, 2024)
Introduction: Maternally inherited diabetes and deafness (MIDD) is caused by the m.3243AG pathogenic variant in maternally inherited mitochondrial DNA. Diabetes is prevalent in our setting; however, MIDD is rarely diagnosed. This study, undertaken in Pretoria, South Africa, highlights the variable presentation of MIDD in different patients within the same family. Case presentation: A 45-year-old man (proband) with hearing impairment was referred to the endocrine unit in July 2015 due to poor glycaemic control (HbA1c = 13%). His clinical and biochemical features were in keeping with MIDD. A genetic study of accessible maternal relatives was pursued. His mother had difficulty hearing and reportedly died from an unspecified cardiovascular cause. Two sisters with diabetes and deafness died of cardiac-related conditions. One nephew had diabetes (HbA1c = 7.7%), hearing loss and tested positive for m.3243AG. A third sister tested positive for m3243AG, but aside from bilateral mild hearing loss in higher frequencies, showed no other signs of target organ damage. Her daughter developed end-stage kidney failure necessitating a transplant, while her son had no biochemical abnormalities and was negative for m.3243AG. Management and outcome: A multidisciplinary team managed and screened for complications of the patient and his maternal relatives. Proband died prior to genetic testing. Conclusion: Most MIDD patients initially present with symptoms of diabetes only, and it is probable that many cases remain undiagnosed. A high index of suspicion is necessary when encountering a family history of both diabetes and impaired hearing, and screening should be offered to the patient's maternal relatives. What the study adds: This study demonstrates the importance of proper assessment when evaluating a patient with diabetes and a family history of hearing loss.